Obtenção de anticorpos monoclonais murinos contra antígenos de Staphylococcus aureus resistentes à meticilina por imunização subtrativa - Simões, Ana Claudia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The MRSA infections are considered a public health problem, with a high mortality rate. Thus, with the wide spread of MRSA it's necessary to embrace monitoring programs to evaluate the sensitivity profile of the isolates, as well as to stimulate technological development aiming faster and more reliable methods to anticipate the choice of the most appropriate therapy by proposing methods of prevention and vaccines to advance the control of hospital infections. Therefore, this study aims the characterization of anti-MRSA monoclonal antibodies obtained by classical immunization protocols and the obtaining of other antibodies with the subtractive immunization method. We used 10 Balb/C mice that received as tolerogen proteins of strains of E. coli and MSSA associated with 100mg/kg/d of cyclophosphamide (Cy) in D1, D2, D3, D 15, D16 and D17. On D+31, 38, 45 and 54 we made injections of 50 μg of the MRSA strain protein, previously genotyped and with confirmed presence of mec A. We prepared antigenic extracts by 3 different methods: boiling, death at ambient temperature followed by 0.22 μm filtration and death at ambient temperature and exposure to ultrasonic wash.The boiling method resulted on average 5.31mg/mL, whereas the technique of death at ambient temperature, filtered or exposed to ultrasonic wash culminated on average in a protein concentration two times higher, indicating the existence of heat labile proteins.We identified a mortality rate of 30% in the animals, which was probably associated with the use of Cy. We performed seven cellular fusions with the construction of 4.402 hybrids with a fusion efficiency rate of 2.42 times smaller than that obtained in protocols of classical immunization.We selected two hybridomas for cloning by the limiting dilution method, whose immunochemical characterization identifies bands of 30 and 50 kDa. The proteomic analysis of protein bands that was recognized by the two clones confirm that the ...

As infecções por MRSA podem ser consideradas um problema de saúde pública, com alta taxa de mortalidade. Desta maneira, com a ampla disseminação do MRSA é necessário adotar programas de vigilância que avaliem o perfil de sensibilidade dos isolados, além estimular o desenvolvimento tecnológico objetivando métodos mais rápidos e confiáveis que antecipem a escolha da terapêutica mais adequada propondo métodos de prevenção e vacinas para o avanço no controle da infecção hospitalar. Diante deste desafio este projeto tem como objetivo a caracterização de anticorpos monoclonais anti-MRSA obtidos por protocolos de imunização clássica e a obtenção de outros anticorpos com método de imunização subtrativa. Foram utilizados 10 camundongos Balb/C que receberam como tolerógeno proteínas de cepas de E.coli e MSSA associados a 100mg/kg/d de ciclofosfamida (CFM) em D1, D2,D3,D15, D16 e D17. Em D+31, 38, 45 e 54 foram feitas injeções de 50μg de proteínas da cepa de MRSA, anteriormente genotipada e confirmada a presença do gene mec A. Foram preparados extratos antigênicos por 3 métodos diferentes: fervura, morte à temperatura ambiente seguida de filtração 0,22μm e morte à temperatura ambiente e exposição ao banho ultrassônico. Pelo método de fervura obteve-se em média 5,31mg/mL enquanto que as técnica de morte a TA ambiente, filtrado ou submetido ao banho ultrassônico obtiveram em média uma concentração protéica duas vezes maior indicando a existência de proteínas termolábeis. Foi identificado uma taxa de mortalidade de 30% nos animais provavelmente associado ao uso da CFM. Foram realizadas 7 fusões celulares com a construção de 4.402 híbridos com uma taxa de eficiência de fusão de 2,42 vezes menor do que aquela obtida nos protocolos de imunização clássica. Dois hibridomas foram escolhidos para a clonagem pelo método de diluição limitante, cuja caracterização imunoquímica identifica...
Keywords: Staphylococcus aureus; Anticorpos monoclonais; Imunização; Drogas - Resistência em microorganismos; Drug resistance in microorganisms